DE Sinc-Collocation Method for Solving a Class of Second-Order Nonlinear BVPs - Ali Eftekhari; Abbas Saadatmandi (Mathematics Interdisciplinary Research, 2021)
In this work, we develop the Sinc-collocation method coupled with a Double exponential transformation for solving a special class of nonlinear second-order multi-point boundary value problems (MBVP). This method attains a convergence rate of exponential order. Four numerical examples are also examined to demonstrate the efficiency and functionality of the newly proposed approach.